54 The Effect of Supplementing Clostat 500 (Bacillus Subtilis PB6) to Yearling Steers in a Commercial Feedyard on Health, Salmonella spp. Prevalence, Feedlot Performance and Carcass Characteristics. (21st September 2022) - Trojan, Sara J; Broadway, Paul Rand R; Burdick-Sanchez, Nicole C; Carroll, Jeff A; Hales, Kristin E; Word, Alyssa B; Karr, Kendall J; Holland, Ben P; Ellis, Guy; Maxwell, Casey; Canterbury, Landon; Leonhard, Tyler; et al.
Abstract: Crossbred beef steers, n = 2, 100; 313 ± 38 kg initial body weight (BW) were used to evaluate Bacillus Subtilis PB6 supplementation to yearling steers. Cattle were blocked by arrival date and assigned randomly to pen within block; pens were randomly assigned to treatment within block. Treatments, replicated in 15 pens/treatment with 70 steers/pen, included: 1) control (CON), diets containing no supplemental direct fed microbials; 2) CLOSTAT (CLO), diets supplemented with 0.5 g/animal/d Bacillus subtilis PB6 (CLOSTAT 500, Kemin Industries, Des Moines, IA). Supplementing CLO decreased morbidity (P = 0.03), 10.38% (CLO) vs. 13.43% (CON), decreased the percentage of cattle treated once for bovine respiratory disease (BRD; P < 0.01), 9.14% (CST) vs. 12.76% (CON), and decreased BRD re-treatment rate (P = 0.03). Mortality did not differ among treatments (P = 0.23). Cattle removed from the study tended to be less for CLO than CON (53 vs. 73 animals, respectively, P = 0.06). The prevalence of fecal Salmonella was not different among treatments, (P ≥ 0.35). Overall fecal Salmonella counts tended to be less for CLO (1.59 log CFU/g) than for CON (2.04 log CFU/g; P = 0.07). Concentration of Salmonella in subiliac lymph nodes did not differ by treatment (P = 0.62); however, mean prevalence of lymph node Salmonella decreased 46% by CLO (28.66% vs. 15.48%, CON vs. CLO, respectively, P = 0.46). With dead animals and removals included, final BW was heavier for CLO steers than CON, (P = 0.05), and average daily gain (ADG; P = 0.08), and gain efficiency (G:F, P = 0.06) tended to be greater for CLO than CON. With dead animals and removals excluded, final BW, ADG, and G:F did not differ among treatments (P ≥ 0.30). Carcass traits were not different between treatments (P ≥ 0.15). Supplementing CLO improved health outcomes of yearling steers.